2017
DOI: 10.19044/esj.2017.v13n5p438
|View full text |Cite
|
Sign up to set email alerts
|

Quantification Des Stocks De Carbone De Trois Pools Clés De Carbone En Afrique Centrale : Cas De La Forêt Marécageuse De La Likouala (Nord Congo)

Abstract: The data of carbon stock of central African swamps forests are very few. This study carried out an assessment of the carbon stock of living biomass and coarse woody debris of three biotopes (flooded forest, seasonal flooded forest, and terra firm forest) of Likouala swamp forest (North of Congo). The average of the carbon stock are 190.72±98.7 tC/ha, 39.69±21.24 tC/ha, and 9.45±6.6 tC/ha respectively for above ground, billow ground, and coarse woody debris. The carbon stock of our swamp forest tends to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 34 publications
3
18
1
8
Order By: Relevance
“…Given the difficulties in estimating their carbon stocks by destructive method, in this study, their biomass was estimated in a non-destructive method. Thus, below ground carbon stocks an average of 39.6 tC.ha -1 in the study area; which is similar to the 39.7 tC.ha -1 found by Bocko et al [48] in the Congo forests. However, several authors have reported that below ground carbon stocks in tropical ecosystems and agrosystems are similar [46,48,49].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Given the difficulties in estimating their carbon stocks by destructive method, in this study, their biomass was estimated in a non-destructive method. Thus, below ground carbon stocks an average of 39.6 tC.ha -1 in the study area; which is similar to the 39.7 tC.ha -1 found by Bocko et al [48] in the Congo forests. However, several authors have reported that below ground carbon stocks in tropical ecosystems and agrosystems are similar [46,48,49].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, in Eucalyptus plantations, the curve has an irregular shape. However, the trees.ha -1 remains higher in classes [10-20] and [40][41][42][43][44][45][46][47][48][49][50].…”
Section: Floristic Diversity In the Study Areamentioning
confidence: 99%
“…A further 0.6-2.5 Pg C is estimated to be stored in the vegetation of the Cuvette Centrale peatlands (Dargie et al, 2017). When compared to adjacent terra firme and seasonally flooded forests, Bocko et al (2017) found that the peatland swamp forests of the Cuvette Centrale had considerably lower aboveground carbon stocks (peatlands swamp forest: 147.7 ± 69.7 t/ha; terre firme forest: 295.3 ± 96.3 t/ha, seasonally flooded forest: 292.3 ± 62.8 t/ha). Differences in forest structure were also noted with the contribution of very large individuals (dbh > 70 cm) to the aboveground carbon stock being much more important in terra firme and seasonally flooded forests, whilst the peatland swamp forests had far fewer very large trees (Bocko et al, 2017).…”
Section: Peatland Carbon Stocks and Cyclingmentioning
confidence: 95%
“…In addition to improving estimates of above and belowground carbon stocks, it is also important to understand the carbon dynamics within tropical peatlands. Bocko et al (2017) quantified the deadwood carbon pool in the swamp forests of the Cuvette Centrale. However, at present there are currently no published studies on gross primary productivity and net primary productivity in the Cuvette Centrale peatlands.…”
Section: Peatland Carbon Stocks and Cyclingmentioning
confidence: 99%
See 1 more Smart Citation